DEVELOPMENT OF STUDENTS THINKING IN STUDYING A FOREIGN LANGUAGE - Smolova, C. O. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with educational-methodical complex that promotes effective lesrning foreign language.